Legal Awareness in Social Media: Between Responsibility and Freedom - Andryawan, Andryawan; Winata, Aryanti Agripina; Naftali, Kearen Elvira (Riwayat: Educational Journal of History and Humanities, 2025)
Information technology is feared to be developing rapidly and bringing significant changes, especially in patterns of interaction with society. However, this development raises various problems, especially among teenagers, such as digital crime and a lack of legal awareness regarding the use of social media. This study aims to examine the forms of legal violations that occur due to a lack of awareness about the use of social media, and to explore the positive and negative impacts of social media on society. The use of social media also involves ethical considerations, such as using proper language, avoiding the spread of negative content, ensuring the accuracy of news, respecting the work of others, and not disclosing personal information. The method employed in this study is normative legal research, a process that involves identifying legal rules, principles, and doctrines to address legal issues. The results of this study indicate that excessive use of social media does not always have a positive impact; rather, it can have the opposite effect, leading to cyberbullying, the spread of false information, and other violations regulated under the ITE Law. However, social media also has positive impacts, such as facilitating communication and the dissemination of information. Increasing legal awareness among teenagers is crucial to ensure they can utilize technology wisely and responsibly, without harming others